Application of the Clavien-Dindo Score in the Classification of Postoperative Complications in Women Undergoing Repeat Cesarean Section in Central Vietnam - Linh Giang Thi Truong; Quoc Huy Vu Nguyen; Duy Trong Tran; Ngoc Bich Thi Tran; Phuc An Si Le; Tu Doan Tran; Le Minh Tam (IMR Press, 2022)
Background: Cesarean section (CS) is the most common performed obstetric surgery world widely. Repeat CS is associated with a variety of complications, including intra-peritoneal adhesion, placenta previa, uterine rupture and cesarean hysterectomy. The present study aimed to determine the characteristics, maternal and fetal outcomes and post-operative complications of pregnant women with repeat CS using Clavien-Dindo classification in the Central Vietnam. Methods: We conducted a prospective study on 1342 women who underwent repeat CS between June 2020 and October 2021 at the Department of Obstetrics and Gynecology, Hue University Hospital, Hue, Vietnam. Numerous risk factors and adverse pregnancy outcomes of repeat CSs were identified and analyzed. Results: Intra-operative complications occurred at a rate of 18.2%, whereas post-operative complications rate was 2.8%. There were statistically significant differences in intra-operative complication rates between the pregnant women who had previously undergone only one CS and those who had previously two or more CSs (p = 0.011, 95% CI 1.9: 1.1-2.9). Among 1342 women who were indicated for repeat CS, thirty-seven women suffered from complications after surgery, accounting for 2.8%, as categorized by Clavien-Dindo. In which grade I accounted for 2.0%, grade II accounted for 0.4%, grade IIIa accounted for only 0.3%. No maternal mortality was reported in this study. Conclusions: Post-operative complications rate of cesarean section is extremely low. Application of the Clavien-Dindo classification in clinical scenario to classify those complications has shown to be highly practical.